Toxicity of cyanobacteria. Organotropy of cyanotoxins and toxicodynamics of cyanotoxins by species - Viktoria Ilieva; Magdalena Kondeva-Burdina; Tzveta Georgieva; Vera Pavlova (Pensoft Publishers, 2019)
As a result of blooming, some cyanobacteria (Microcystis, Anabaena, Planktothrix, etc.) produce toxins at concentrations that are high enough to poison and even kill animals and humans. According to Annex II of the Framework Directive 2000/60/EC, transformed into the Bulgarian legislation, for the characterization of surface water, at this stage, there are no acceptable limit values for cyanotoxins. Cyanotoxins include some of the strongest natural poisons, including those that could cause rapid death due to respiratory failure. The aim of this publication is an overview of toxic cyanobacteria and toxicity mechanisms.